PENGARUH PINJAMAN TUNAI DALAM KAPASITAS PENAWARAN PRODUK JASA TERHADAP FLUKTUASI PERMINTAAN KREDIT PELAKU USAHA KECIL PT. PERMATA FINANCE CIKUPA - Nurhadi, Nurhadi (Universitas Bina Sarana Informatika, 2015)
Credit is not foreign to the rapid economic growth higher in terms of supply and demand higher economic wheel rotates, the higher the economic fluctuations in macro it is a momentum shift melinium 2000 mega trends. banking act no. 10 of 1998 explains the